Visual digital intermediaries and global climate communication: Is climate change still a distant problem on YouTube? - Alexandra Segerberg; Matteo Magnani (PLoS ONE, 2025)
This article addresses the role of digital intermediaries in visual climate communication, and specifically their contribution to the persistence of a ‘green ghetto’ of traditional communicators and repertoires online. We argue for a comparative sensibility: global platforms convey global issues to global audiences, yet the same platform may distribute conditions of visibility for compelling communication unevenly around the world. The study analyses how a major global visual platform, YouTube (Search), articulates climate change in 232 countries in their official languages. It combines API research, channel coding and computational image analysis to assess the processing and presentation of top-ranked results with respect to their diversity and proximity to local context. The findings show that YouTube Search establishes visibility winners who typically sustain the classic visual repertoire of climate change as a distant problem, and that Global North sources dominate irrespective of region. However, there are notable exceptions to these patterns.